Analisis Strategi Pemasaran Deposito untuk Meningkatkan Dana Pihak Ketiga di Bank BJB Cabang Sumber - Vinda Reviana; Muhammad Syaefulloh; Dwi Harini; Nur Afridah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the marketing strategy for deposit products to increase Third Party Funds (DPK) at Bank BJB's Sumber Branch. Deposits are a crucial component of banking operations, serving as the primary source of bank financing for lending and investment activities. In an era of increasingly competitive banking industry, particularly with the development of technology-based financial services (fintech), conventional banks are required to have innovative, adaptive, and customer-oriented marketing strategies. This study uses a descriptive qualitative approach to describe the phenomena in depth. Data were collected through direct field observations, in-depth interviews with internal bank personnel, and documentation related to the strategy and implementation of deposit product promotions. The analytical technique used in this study was a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to evaluate the current marketing strategy and formulate future improvement measures. The results show that Bank BJB's Sumber Branch possesses several internal strengths, such as high public trust, close ties with the local community, and competitive and flexible deposit products. However, several weaknesses also exist, such as limited use of digital media and suboptimal financial product literacy among some customers. Externally, opportunities that can be exploited include increased public interest in safe investment products, while threats come from fintech competition offering similar products in more practical ways. Based on these findings, deposit product marketing strategies need to be directed at strengthening digital promotion, improving customer financial literacy, and developing more personalized services. This is expected to significantly increase third-party funds (DPK) and maintain sustainable bank growth amidst the current dynamics of the financial industry.